Gigabit-capable passive optical networks - Hood, Dave, 1945- (Wiley, 2012)
Gigabit-capable passive optical networks (G-PON) have a large and increasing base of support among telecommunications operators around the world. Written by two of the experts in the field, this book explains G-PON in detail. As well as a history that clarifies the reasons for many of the existing features, the book looks at current and evolving technology and discusses some of the alternatives for future access networks.